Front page - AIC ICMSA 2016 - AIC Committe AIC Committe (Proceedings of AICS - Social Sciences, 2016)
The Annual International Conference (AIC) conference is a forum of information distribution,scientific discussion of literature, research, innovative and sustainable technology, industryproduct, etc. The AIC activity has been carried out regularly by Unsyiah since 2011. This year,the university will host The 6th Annual International Conference (AIC) in conjunction with The12th International Conference on Mathematics, Statistics and Their Application (ICMSA).Furthermore, in this year The AIC program will also deliver an Innovation Expo and IndustrialForum event.